1990
DOI: 10.1088/0957-0233/1/12/012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic quantities of a cascade arc used as a light source for spectroscopic techniques

Abstract: Abstract.We have determined the characteristic quantities (the electron temperature and the electron density) of an argon plasma in a cascade arc (diameter of 2 and 4 mm) for a pressure range of 1 x 105-8 x IO5 Pa and a current range of 20-70 A. The absolute continuum intensity was also determined in the wavelength ranges from 250-320 nm and 380-800 nm for pressures of 2, 4 and 6 bar and 20, 40 and 60 A in the case of a 2 mm arc. The plasma is close to local thermal equilibrium (LTE). Using the mentioned quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 5 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…14 -16 A detailed description of the light source was given by Wilbers et al 15,16 and by Raghavan et al 14 The light source used is operated with argon at pressure of 1.8 bar and argon flow of 10 sccm. The operating current was set to 25 A and the light that exited the window of the arc is KBr with a thickness of 4 mm.…”
Section: A Light Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…14 -16 A detailed description of the light source was given by Wilbers et al 15,16 and by Raghavan et al 14 The light source used is operated with argon at pressure of 1.8 bar and argon flow of 10 sccm. The operating current was set to 25 A and the light that exited the window of the arc is KBr with a thickness of 4 mm.…”
Section: A Light Sourcementioning
confidence: 99%
“…͑It is known that changing the gas from argon to xenon has a positive influence on the light intensity. 15 ͒ Increasing the arc current has a strong influence on the light intensity, an increase of 10% in the current results in an increase of 10% in the light intensity emitted. A 10% increase of gas pressure however results in only a 5% increase of emitted light intensity.…”
Section: A Light Sourcementioning
confidence: 99%
“…Another complication in this study is the presence of a signal at the spectrometer detector generated by plasma photons: the cascaded arc plasma source, which produces a large photon flux covering the total spectral range, 45 is perfectly aligned with the mass spectrometers orifice ͑see Fig. 1͒.…”
Section: Ion Mass Spectrometrymentioning
confidence: 99%
“…Previous research shows that the cascaded arc is an ideal design to create a stable arc plasma with high electron density as well as an expanding plasma for both plasma studies and applied research. 13,14 It has been shown that the expanding cascaded arc plasmas have potential prospect in different application fields; e.g., using a cascaded arc as a light source for spectroscopy, 15 as a particle source for surface modification,13 silicon thin film deposition, 16 carbon thin film deposition 17 and passivation protection technique for archaeological artefacts. 6 Mostly noble gases are used to feed the arc plasma, but exceptionally molecular gases like H 2 and SF 6 are added.…”
Section: Introductionmentioning
confidence: 99%